Continuous and comprehensive atmospheric observations in Beijing: a station to understand the complex urban atmospheric environment. Issue 3 (2nd July 2020) - Liu, Yongchun; Yan, Chao; Feng, Zemin; Zheng, Feixue; Fan, Xiaolong; Zhang, Yusheng; Li, Chang; Zhou, Ying; Lin, Zhuohui; Guo, Yishou; Zhang, Ying; Ma, Li; et al.
ABSTRACT: Due to profound impact on climate and human health, air quality has attracted attention from all levels of the civil society. The key step in the provision of required tools for the society to tackle the complex air quality problem is to characterize it in a comprehensive manner with a long-term perspective. Here, we describe a continuous and comprehensive observation station and its accompanying state-of-the-art instrumentation that was established to investigate the complex urban atmospheric environment in a rapidly developing Chinese Megacity. The station, located in downtown Beijing, aims to study air quality by identifying the major atmospheric pollutants and key processes determining their formation and loss mechanisms. A few hundreds of parameters are continuously measured with the state-of-the-art instruments, including trace gas concentrations, aerosol particle size distributions, and mass concentrations, covering aerosol particle chemical composition from molecules to micrometer-sized aerosol particles. This produced long-term, comprehensive big data with around 1 × 10 11 bytes per year. In this paper, we provide an overview on the facilities of the station, the instrumentation used, the workflow of continuous observations and examples of results from 2018 to 2019 and a basis for establishing a modern long-term, comprehensive atmospheric urban observation station in other megacities.